Accuracy of a Topical PET/CT Scanner on SUV Measurements of Small Volumes SUV - Frank Schelper, Lutz; Oeri, Milan; Buchmann, Inga (Current Medical Imaging, 2015)
Aim: The subject of our study is to investigate the accuracy of a typical PET/CT system applying 18F-FDG to determine activity of small, hot volumes (HV) by phantom measurements under the impact of reconstruction techniques (RT) with and without Time-of-flight-Mode (TOF), activity concentration ratios into the phantom (ACR), density variations and relevant analysis parameters. Methods: We investigated a body phantom containing up to 7 spheres (d = 6-37mm) on a topical PET/CT system (SIEMENS BIOGRAPH mCT40). Recovery coefficients (RC) of small HVs dependent on the ACR and several RTs (iterative default (IT), iterative high-definition including the system Point-Spread-Function (HD), HD+TOF (UHD), filtered backprojection (FBP) and FBP+TOF (FBPT) were analysed. In addition, we determined RCs with respect to the matrix size, number of iterations, filter settings and a phantom insert of lung and bone density equivalent material. Results: The application of UHD in particular reproduces true activities of small volumes best, followed by HD, IT, FBPT and FBP. Lung and bone equivalent density inserts reduce the RCs by up to 19%. Especially for small HVs the RC can be raised by increasing the matrix size and iterations. Conclusions: Novel technology and analysis have a strong impact on the quantification. Hence, new guidelines are required enabling comparisons to other, prior systems. In order to get a precise activity determination of small structures, we recommend the UHD algorithm, high resolution matrix and high number of iterations with respect to acquisition time and administered activity.
Keywords: recovery